Strengthening knowledge sharing and job dedication: The roles of corporate social responsibility and ethical leadership. Issue 1 (10th January 2020) - Liu, Min-Ling; Lin, Chieh-Peng; Chen, Mei-Liang; Chen, Pei-Chun; Chen, Kuang-Jung
Abstract : Purpose: The purpose of this paper is to propose a moderated mediation model to explain how corporate social responsibility (CSR) and ethical leadership influence knowledge sharing and job dedication through the mediating mechanism of positive affective tone and cognitive meaningfulness. Design/methodology/approach: The research hypotheses were empirically tested using a survey of employees from the high-tech industry in Taiwan. The research constructs in this study were measured using five-point Likert scales modified from existing literature. The survey data were empirically analyzed with two-step structural equation modeling (SEM) and regression analysis. Findings: The empirical results of this study reveal that CSR and ethical leadership positively relate to positive affective tone and cognitive meaningfulness. Knowledge sharing is positively affected by positive affective tone whereas job dedication is positively affected by positive affective tone and cognitive meaningfulness. While the relationship between positive affective tone and job dedication is positively moderated by job demand, the relationship between cognitive meaningfulness and job dedication is negatively moderated by job demand. Originality/value: This study elucidates the ethical influences from organizations (i.e. CSR) and leaders (i.e. ethical leadership) respectively to explain affective and cognitive processes involved in work situations. At the same time, by clarifying the moderating role of job demand, this study provides valuable implications for managers to effectively leverage job demand for increasing employees' job dedication.